A low-voltage gain boosting-based current mirror with high input/output dynamic range. (August 2019) - Doreyatim, Mohamadsaeed; Akbari, Meysam; Nazari, Masoud; Mahani, Sina
Abstract: This paper presents a bulk-driven current mirror circuit based on the gain-boosting technique to achieve high input/output dynamic range and high output resistance. The bulk-driven based diode-connected transistor at the input removes the threshold voltage limitation to provide low headroom voltage on the basic transistors. In addition, the auxiliary circuit used in the first gain-boosting structure is a current mode amplifier that is driven by draining current from the main circuit to remove threshold voltage limitation on the input/output swing. In order to achieve higher output resistance, the second gain-boosting structure includes a voltage mode amplifier without creating any limitation on the output swing. Simulation results in a 0.18 ​μm CMOS technology show a maximum output voltage swing of 0.9 ​V under a 1 ​V supply, while the input and output resistances are 68.3 ​Ω and 10.5 ​GΩ, respectively. The current transfer error also changes between −0.085% and +0.075% for an input current range of 1000 ​μA.